THE ROLES OF ISLAM IN MALCOLM X’S PERSONALITY AND IDENTITY RECONSTRUCTION AS A MOSLEM AFRICAN AMERICAN: A PSYCHOANALYSIS APPROACH - Nor Faizah Kaeni (British : Jurnal Bahasa dan Sastra Inggris, 2022)
The study is to analyze the role of Islam in Malcolm X’s personality development and identity reconstruction by applying psychoanalysis approach. The method of the study was descriptive analysis by reading and rereading the text; Autobiography of Malcolm X, several times in order to gain data representing Malcom X’s Islamic experiences and thoughts which help him complete his understanding on his identity and perspectives towards white Americans and racism problems in America. Possesing multiple parts of identity, Malcolm X has to face the reality of identity confusion. The experience of understanding Islam has contributed to the development of the Id, Ego, and Superego in building concept and perspectives towards himself as African American and also white people. His life experiences have contributed to his Id’s wishes of gaining identity and recognition. In addition, they alco contributes to Superego’s full and complete concept of his identity as a Moslem, an African, as well as an American. Meanwhile, Ego is able to find balance between Id and Superego’s  force which encourages him to comprehend his identity and even formulate thoughts on racism through Islamic perspectives. Islam has helped Malcolm X achieve a whole understanding on his multiple identity as a Moslem, as an African descendant and even part of American citizen.. Keywords: Islam, personality, identity reconstruction, moslem African American, psychoanalysis